Principal Leadership Model at Muhammadiyah Junior High School of Surakarta City - Istanto Istanto; Fakhruddin Fakhruddin; Heri Yanto; Hesti Dwi Setyowati (International Conference on Science, Education, and Technology, 2021)
In the city of Surakarta, there are many schools under the auspices of Muhammadiyah. However, even though they are both under Persyarikatan Muhammadiyah, there are gaps in terms of quality and quantity between one school and another. This is possible because of the differences in the leadership model used by each school principal. The aim of this study is to analyze the leadership model in Muhammadiyah Junior High School of Surakarta and describe the result of the application of the model, so get the result of the description model of leadership principals in Muhammadiyah Junior High School of Surakarta City and achievement of results. The subjects of this study were all Muhammadiyah Junior High School in Surakarta, which amounts to 9 schools, based on observations beginning of each school has different qualities though under the auspices of the same organization. This study uses qualitative methods with data collection techniques in observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman model, consisting of data reduction, data presentation, and conclusions. The validity of the data using source triangulation and technical triangulation. The results showed that almost all Muhammadiyah junior high school principals in Surakarta City used the Fiedler contingency model, the Vroom and Yetton model, and the Path-Goal Theory model. The difference lies in style used in each of these models. Then the results of the application of these models are the results in the development of human resources, maintaining the number of students, the achievement of family relations and the welfare of subordinates, development of infrastructure, development of innovation, and improvement of achievement.